1999
DOI: 10.1103/physrevlett.82.2254
|View full text |Cite
|
Sign up to set email alerts
|

CPTand Lorentz Tests in Hydrogen and Antihydrogen

Abstract: Signals for CPT and Lorentz violation at the Planck scale may arise in hydrogen and antihydrogen spectroscopy. We show that certain 1S-2S and hyperfine transitions can exhibit theoretically detectable effects unsuppressed by any power of the fine-structure constant. [S0031-9007(99) PACS numbers: 11.30. Er, 12.20.Fv, 32.10.Fn, 32.80.Pj Experimental and theoretical studies of the spectrum of hydrogen (H) have historically been connected to several major advances in physics [1]. The recent production and obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
343
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 352 publications
(359 citation statements)
references
References 36 publications
15
343
0
1
Order By: Relevance
“…Nonetheless, it was shown that signals for CPT symmetry and the Lorentz violation at the Planck scale may arise in hydrogen and antihydrogen spectroscopy [7]. Effects of this type can appear in H andH spectra at zeroth order in the fine-structure constant and are detectable not only in spin-mixed 1s-2s lines but also in spin-flip hyperfine signals.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it was shown that signals for CPT symmetry and the Lorentz violation at the Planck scale may arise in hydrogen and antihydrogen spectroscopy [7]. Effects of this type can appear in H andH spectra at zeroth order in the fine-structure constant and are detectable not only in spin-mixed 1s-2s lines but also in spin-flip hyperfine signals.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 1S −2S transition line is the ultimate experimental goal, CPT -violating effects may also appear in other hydrogen energy splittings [15]. Other attractive comparative measurements include, the 2S 1/2 − 2P 1/2 Lamb shift [1] and the ground-state hyperfine structure [16][17][18].…”
Section: Precision Comparison Of the Properties Of Hydrogen And Antihmentioning
confidence: 99%
“…The SME is a dynamical model constructed to contain all Lorentz-and CPT-violating lagrangian terms consistent with coordinate independence, which is a fundamental requirement to be discussed below. To date, numerous Lorentz-and CPT-violation tests involving hadrons [8][9][10][11][12][13][14][15][16][17][18][19][20][21], protons and neutrons [22][23][24][25][26][27][28][29][30][31], electrons [31][32][33][34][35][36][37][38][39][40][41], photons [42][43][44][45][46][47], muons [48][49][50], and neutrinos [2,[51][52][53][54] have been analysed or identified within th...…”
Section: Motivationmentioning
confidence: 99%